Haematological Alterations in Cattle Infected with Trypanosoma evansi - Pandya, SS; Hasnani, JJ; Hirani, ND; Patel, PV (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This study was performed to unmask the haematological alterations in Trypanosoma evansi infected cattles. Blood samples from 50 Trypanosoma infected and 50 non-infected from Anand and Mahisagar districts were collected for the present study. Animals were bled from the jugular vein into 10 ml vacutainers containing EDTA for the estimation of various haematological parameters. The haematological parameters of cattle infected with T. evansi revealed decreased Hb, PCV, TEC, MCV, MCH and blood glucose level also (40.67±1.71 vs. 70.76±1.73 mg/dl), and increased TLC and MCHC than those of non-infected healthy cattle. The neutrophil and eosinophil counts were significantly increased (P
Keywords: Blood; Cattle; Trypanosomiasis; Haematological alterations